Water for elephants - Gruen, Sara, 1969- (Two Roads, 2011)
Jacob Janowski's luck had run out-orphaned and penniless, he had no direction until he landed on a rickety train that was home to the Benzini Brothers Most Spectacular Show on Earth. A veterinary student just shy of a degree, he was put in charge of caring for the circus menagerie. It was the Great Depression and for Jacob the circus was both his salvation and a living hell. There he met Marlena, the beautiful equestrian star married to August, the charismatic but brutal animal trainer. And he met Rosie, an untrainable elephant who was the great hope for this third-rate traveling show. The bond that grew among this group of misfits was one of love and trust, and ultimately, it was their only hope for survival.